(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The article examines the experience of developing a Russian language training course for migrant workers: the features of building this course, the target group, the regulatory framework and the problems arising during the implementation of this course. The interpretation of existing methodological terms relevant for the purposes of teaching Russian as a non-native language provides recommendations for teachers working in the classroom of migrant workers.